Super-resolution GaAs nano-structures fabricated by laser direct writing. (September 2018) - Zhang, Wei; Shi, Zhenwu; Chen, Chen; Yang, Xinning; Yang, Linyun; Zeng, Zhongming; Zhang, Baoshun; Liu, Qian
Abstract: Nanostructures have been applied in various semiconductor devices. However, current nanostructure fabrication technologies always have such or that shortages, stimulating a need for new technology with simple fabrication, high efficiency and low cost. In this paper, we present super-resolution nanostructure fabrication based on laser ablation effects by using laser direct writing technique. GaAs nanostructures including nano-holes, nano-grooves and gratings have been fabricated. The depths and full widths at half maximum of nano-grooves show linear dependence on laser power and pulse duration. The minimum full width at half maximum of grating groove reaches to 32 nm, which is nearly 1/10 to diameter of focused laser spot. The results demonstrate the capacity of laser direct writing technique and provide a simple means for super-resolution nanofabrication.